Semiotics of Home Sweet Loan Movie: Family Representation and Communication - Rosa Marcella; Agnest Aprillia; Aghnia Dian Lestari (International Journal of Business, Economics, and Social Development, 2025)
Family communication is one of the most important aspects in creating a harmonious family environment. This research aims to find out the picture of family communication in the movie Home Sweet Loan through semiotics using Charles Sanders Peirce's theory. There are 10 scenes that represent family communication. Each scene in this movie will be decomposed into signs, objects, and interpretations that describe the complex dynamics of communication regarding the challenges faced by large families in maintaining harmony and balance in the family. This research is descriptive with a qualitative approach based on Charles Sanders Peirce's semiotic theory. Data collection techniques in this research include observation, interviews with Home Sweet Loan movie viewers, and documentation. Observations were made at the Home Sweet Loan movie, and in-depth observations were made through the Home Sweet Loan Press Conference. Based on the 10 scenes taken by the author to be observed, the findings obtained are Sign, interaction that shows the communication process established in the Kaluna family, Object a cut picture of the Kaluna family, Interpretant a picture of communication in the film about the reality of the family displayed and felt by the audience.